The biology of two important by-catch skate species on the Agulhas Bank, South Africa - Walmsley, Sarah Ann (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 1997)
Members of the family Rajidae are common components of the demersal trawl fishery, contributing around 1% to the total catch. However, apart from a single species all South African rajids are currently discarded. With demands for new protein sources ever-increasing, it is possible that currently underutilised species, such as the skates will be utilized to a greater extent. Raja wallacei and R.pullopunctata are common trawler by-catch species, ranging along most of the South African coast. The current study allred to further knowledge on the population biology of both species through age and growth, reproductive and feeding studies. The study also allred to assess whether any of the South African skate species show the potential for utilization as a food source. Band counts of vertebral centra were used to determine growth parameters and generate growth curves for males and females of both species. Growth was significantly different between the sexes. In both cases, females grew slower than males but reached a greater asymptotic disc width. As with other elasmobranchs, R.wallacei and R.pullopunctata are long-lived and slow growing. As with all other skates, the study species are oviparous laying large, yolked eggs in tough, leathery cases on the sea bed. The onset of maturity occurs at a large size (approximately 400mm disc width (10-11 years of age) for R.wallacei and 600mm disc width (12-13 years of age) for Rpullopunctata) and is very rapid. The oldest R.wallacei and R.pullopunctata observed were 16 and 18 years of age, respectively. No distinct breeding season was determined and no nursery areas were observed. A large proportion of individuals, especially R.pullopunctata was immature. Both species fed primarily on crustaceans and teleosts with an ontogenetic shift in diet from mysids, amphipods, isopods and bregmatocerids to larger Gnathophis sp., Mursia cristimanus and carid shrimps. Large discrepancies were seen in the diet of animals spatially, temporally and between research and commercially-caught animals. Disc-width frequency data was limited but suggested that both species show preference for depths of 100-300m. Size distribution did not appear to be affected by depth, although the data set was limited. A paucity of large individuals in the catch may indicate that stocks are suffering from growth overfishing by trawling operations. Historical and observer data showed that although skates are common components of the by-catch, the potential for greater use is limited. The biscuit skate, R.straeleni, on the west coast is the only species that could be better utilized. If skates are treated as a single group the potential is increased but this causes problems in assessing stocks.
Keywords: Skates (Fishes) -- South Africa -- Physiology